PERBANDINGAN LATIHAN TWO IN-FORWARD DAN LATIHAN DIAGONAL STEP:ONE IN,ONE OUT-FORWARD TERHADAP KETERAMPILAN MENGGIRING BOLA PEMAIN TIM SSB GENARI SMR PEKANBARU - Arnando, Jeimmy.S. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Method which using research Experiment. This Research use data analysis bystatistic. Population in this research team of SSB Genari SMR Pekanbaru exercisingForestry football ground of Panam, with amount of sampel that is 20 people ofsampel.This research team of SSB Genari SMR Pekanbaru exercising Forestry field,because seen from ability had about skill of athlete in dribbling ball which owning byathlete of SSB Genari SMR U 15 still not yet gratified. So that researcher wish tocheck this team by giving treatment of practice of Two Diagonal practice and in-forward of Step:One out-forward in,One. Where data can be obtained and collectedto tes early and final tes that is Tes Dribble Ball, before and after giving practice ofTwo Diagonal practice and in-forward of Step:One ou-forward in,One, as a mean toKnow Influence of this Method Practice To Skill Dribble Ball player of team of SSBGenari SMR Pekanbaru.From result of data analisi indicate that there are comparison of influencewhich signifikan practice method of Two Diagonal practice and in-forward ofStep:One out in,One to skill dribble team ball of SSB Genari SMR Pekanbaru.Pursuant to result of calculation of analysis statistic test t yield group thitung of Aequal to 3,57, group of B equal to 3,80 with ttabel 1,833, at group of A and group ofB equal to 4,15 with ttabel 1,734 at level of signifikan 0,05. Meaning thitung > ttabelso that can be taken conclusion that third hypothesis accepted, hence practice of TwoDiagonal practice and in-forward of Step:One out-forward in,One can uplift skill todribble ball. Make-Up of mean 0,50 at group of A and 0,57Keyword : Method Practice of Two Diagonal practice method and in–forward of Step:One out-forward in,One, dribbling ball.